FUTURE DATA CENTERS: LIQUID IMMERSION COOLING INNOVATION TO WITHSTAND AI HEAT - Aom Thai; Pong Krit; Siri Lek (Journal of Computer Science Advancements, 2025)
The exponential escalation of computational density required by modern Artificial Intelligence (AI) and Large Language Models has pushed traditional air-cooled data center infrastructures to their thermodynamic limits. This study investigates the efficacy of single-phase liquid immersion cooling as a transformative solution to manage the extreme thermal flux of next-generation AI accelerators. Adopting a quantitative experimental design, we benchmarked a high-density GPU cluster submerged in a proprietary dielectric fluid against a standard forced-air baseline under intensive MLPerf training workloads. The research focused on evaluating key performance indicators, including Power Usage Effectiveness (PUE), processor junction temperatures, and total energy consumption over a 168-hour stress test. Results demonstrate that the immersion architecture achieved a near-ideal PUE of 1.04, representing a 34% efficiency improvement over the air-cooled control group. Furthermore, the liquid medium maintained GPU core temperatures 20°C lower than the baseline, effectively eliminating thermal throttling events and enhancing computational stability. The study concludes that shifting from aerodynamic to hydrodynamic cooling is not merely an efficiency upgrade but a physical prerequisite for the sustainable scaling of exascale AI infrastructure, offering a viable pathway to decarbonize the expanding digital economy.